2004
DOI: 10.1017/s0022112004009553
|View full text |Cite
|
Sign up to set email alerts
|

The optical distortion mechanism in a nearly incompressible free shear layer

Abstract: The aero-optical distortions caused by compressible flows have been used by researchers for flow diagnostics and accepted by designers of airborne optical systems as a performance penalty. In order to estimate these distortions, an understanding of the optical distortion mechanism is required. This article examines the mechanisms which produce a variable-density field (and accompanying index-of-refraction field) in a nearly incompressible shear-layer flow. The two-dimensional-shear-layer velocity field was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 65 publications
(126 reference statements)
3
97
0
Order By: Relevance
“…As vortices are kept round throughout their evolutions, an inner shear layer vortical structure is not resolved. Since only few large vortical structures are present at any moment of time in the computational region, it greatly expedites computational times to solve model's governing equations (2). The model was intensively tested and it was found to correctly predict mean flow quantities and spatial-temporal characteristics of optical distortions caused by a shear layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As vortices are kept round throughout their evolutions, an inner shear layer vortical structure is not resolved. Since only few large vortical structures are present at any moment of time in the computational region, it greatly expedites computational times to solve model's governing equations (2). The model was intensively tested and it was found to correctly predict mean flow quantities and spatial-temporal characteristics of optical distortions caused by a shear layer.…”
Section: Discussionmentioning
confidence: 99%
“…These structures continue to pair and merge downstream, thus the shear layer growth increases downstream. An example of a vorticity field in a 2-D transonic shear layer computed using a Weakly Compressible Discrete Vortex Model (DVM) 2,5 , is given in Figure 1. In this example, the vortical structure appears around 0.2 m and the first and the second pairing can be observed at x = 0.53 and 0.74 m, consequently.…”
Section: And References Therein)mentioning
confidence: 99%
See 1 more Smart Citation
“…The Notre Dame efforts have moved the understanding of aero-optics from a statistically-based, time-averaged, optical-pathdifference (OPD) approach, based on statistical, fluid-mechanical measurements, to a formal, cause-and-effect understanding of optical propagation through boundary and shear layers. [1,2,3] The work reported here made use of the results of these previous grants, in particular the knowledge of the aberrating physics, various high-bandwidth wavefront-sensing instruments developed at Notre Dame, techniques developed using other commercially-available instruments, and our high-bandwidth deformable mirror, acquired under a DURIP grant as part of our high-bandwidth adaptive optics system to demonstrate the historic adaptive-optic correction of a laser beam projected through a Mach 0.8 shear layer. This demonstration took place at the very beginning of the present grant.…”
Section: Sponsoring / Monitoring Agency Name(s) and Address(es)mentioning
confidence: 99%
“…It has been found that the physical mechanism for optical aberrations in a free shear layer are the low pressure wells (and their concomitant density wells) associated with the coherent vortical structures that roll-up naturally in the free shear layer 2 . It has been proposed that a similar mechanism is responsible for the optical aberrations in a turbulent boundary layer.…”
Section: Introductionmentioning
confidence: 99%